Empathic Communication in Digital Spaces: Supporting the Mental Health of Cancer Patients - Ade Rahmawati Siregar; Dewi Kurniawati; Nurbani; Raras Sutatminingsih (Jogjakarta Communication Conference (JCC), 2026)
The importance of verbal and nonverbal communication approaches in digital spaces has become a communication approach used worldwide. This communication approach can be linked to the mental health outcomes of patients with chronic illnesses such as cancer. In communication, empathy means trying to understand another person's perspective on what they are saying. Previous research has analyzed various communication approaches in digital spaces, particularly in relation to the mental health outcomes of cancer patients, but these studies remain limited. The primary objective of this qualitative research study was to explore empathic communication in digital spaces among cancer patients in Medan, Indonesia. Data were collected through semi-structured interviews and an analysis of empathic communication perspectives. The analysis revealed that cancer patients struggling to survive rely heavily on verbal communication, through direct guidance and information that can directly motivate them to fight cancer, and non-verbal communication, through text or scenes that also inspire their enthusiasm for surviving the disease. Therefore, it is recommended that an application be developed specifically to assist cancer patients segmented by age, gender, and profession so they can easily access detailed information about empathetic perspectives to achieve mental health.